ABOUT TEXTUAL RESEARCH IN WORLD LINGUISTICS (Scientific journal of the Fergana State University, 2024)
This article outlines scientific views on text linguistics. The text has become the object of study in many schools of linguistics, and the concept of text is interpreted differently in traditional and modern linguistics. In world linguistics, including Turkic studies, Russian, German, French, and Czech linguistics, it is noted that scientific researches and specific directions are taken as an object of study within the text. The article analyzes text theory in world linguistics, general and integral aspects of text linguistics, formation and development, the concept and interpretation of text.